Orthodox constructions of the West - Demacopoulos, George E.; Papanikolaou, Aristotle (Orthodox Christianity and contemporary thought., 2013)
The category of the "West" has played a particularly significant role in the modern Eastern Orthodox imagination. It has functioned as an absolute marker of difference from what is considered to be the essence of Orthodoxy, and, thus ironically, has become a constitutive aspect of the modern Orthodox self. The essays collected in this volume examine the many factors that contributed to the Eastern construction of the West in order to understand why the West is so important to the Eastern Christian's sense of self.